Farmacoeconomic impact of anti-TNFα - E. Vaccaro; C. Bernardi; G. Leardini (PAGEPress Publications, 2011)
The anti-TFNα are undoubtedly an efficacious cure in the treatment of rheumatoid arthritis, but their costs are so high that a thorough pharmacoeconomical evaluation is needed in order to identify the specific conditions in which their use is to be considered convenient. For this reason there are related the most important experiences that have studied the cost-efficacy and cost-utility relationships of anti-TFNα drugs, which have been made marketable in Italy. The data available, unfortunately, are too various to allow a final settlement of the chart of convenience between the different therapeutic alternatives. Moreover the socio-medical reality in Italy is so much different from the ones in other countries that it is impossible to try and use the foreign experiences. In a country of high social commitment like Italy, a fair judgment can thereafter be made only when the issue is considered related to our society, taking in account the summation of the medical costs endured by the National Health System, the patient's expenses and the ones that are a consequence of the loss of productivity.